(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Leal JS, Pabiona MG, Cristobal JU, Melencion AB, Labajo JRN. 2025. Effects of iron supplementation rates and time of application on iron biofortification and macronutrient uptake in radish (Raphanus sativus) microgreens. Asian J Agric 9: 94-102. This study investigates strategies to enhance iron biofortification in radish (Raphanus sativus) microgreens through various iron supplementation rates and application timings. The primary objectives were to evaluate fresh weight at harvest and iron absorption efficiency under different treatment conditions. Results demonstrated significant variations in fresh weight, with microgreens treated with SNAP + 10 ppm iron chelate six days post-blackout (A1B3) yielding the highest fresh weight (149.38 g), while those treated four days post-blackout showed the lowest weight (113.54 g). In terms of iron content, treatment A2B1 exhibited the highest concentration (247.78 ppm), whereas A1B2 recorded the lowest (185.03 ppm). The study highlights the intricate relationship between iron supplementation levels (Factor A) and application timing (Factor B) concerning growth and nutrient uptake dynamics in radish microgreens. Overall fresh weight did not differ significantly across iron levels, based on iron concentration x application timing. Moderate iron concentrations initially supported fresh weight, but excess levels hindered growth, emphasizing the delicate balance required in iron supplementation strategies. Nitrogen uptake benefited from moderate iron levels and delayed application, while phosphorus and potassium assimilation were optimized with timely nutrient supply (p<0.05). Notably, total potassium content varied significantly (p<0.05), peaking at 20 ppm iron, suggesting iron’s facilitative role in potassium uptake up to a threshold. Moreover, iron content in microgreens remained stable across tested concentrations but significantly increased with specific application timings, underscoring the importance of precise nutrient management for effective iron biofortification. These findings contribute to advancing tailored nutrient management practices to optimize growth, nutrient uptake dynamics, and iron biofortification in radish microgreens. Future research directions should explore underlying physiological mechanisms to refine strategies for sustainable crop production and enhance nutritional quality.